Plasmonic light harvesting of dye sensitized solar cells by Au-nanoparticle loaded TiO2 nanofibers - Naphade, Rounak A.; Tathavadekar, Mukta; Jog, Jyoti P.; Agarkar, Shruti; Ogale, Satishchandra (Journal of Materials Chemistry A, 2014)
We report a significant enhancement in the performance of dye sensitized solar cells by using in situ Au nanoparticle (Au NP) loaded TiO2 nanofibers (Au: TiO2 NFs) as the light harvesting (LH) layer as compared to the use of only TiO2 nanofibers (NFs) as the LH layer. The Au NP: TiO2 nanofibers are prepared by electro-spinning of a precursor mixture whereby nanostructured porous TiO2 nanofibers are formed and get in situ loaded with only 4-5 nm AuNPs. The as-synthesized nanofibers are characterized by X-ray diffraction, Raman, photoluminescence (PL) and Mott-Schottky analyses. The presence of gold nanoparticles shows considerable improvements in light harvesting and the electrochemical properties of TiO2 nanofibers. A remarkable enhancement in the efficiency by 25% is achieved with the AuNF LH layer as compared to 12% with the NF layer, over the value without any light harvesting layer. The IPCE and impedance analyses reveal commensurate improvements. The impedance study shows a decrease in the transport resistance (R-TiO2) and an increment in the chemical capacitance and life time of the solar cell. Systematic analyses of the optical properties suggest that the enhanced light harvesting by Au NP loaded TiO2 nanofibers is caused by the role of plasmon-polariton modes at the distributed nanoscale Schottky junctions in the Au: TiO2 nanofibers.

Minute-made activated porous carbon from agro-waste for Li-ion battery anode using a low power microwave oven - Agarkar, Shruti; Yadav, Poonam; Fernandes, Rohan; Kothari, Dushyant; Suryawanshi, Anil; Ogale, Satishchandra (Electrochimica ACTA, 2016)
We demonstrate a very simple, cost-effective and superfast process for making Li-ion battery (LIB) anode grade carbon from agro-waste in the form of sugarcane bagasse using a low power microwave system. Activation of this bagasse derived carbon is carefully optimized by using various weight ratios of KOH to obtain the desired properties of functional carbon in terms of porosity and electrical conductivity. Low equivalent series resistance (ESR), low charge transfer resistance with good electrical conductivity, and optimum porosity for efficient ion diffusion make this carbon a good candidate for Li-ion battery anode material rendering a reversible capacity of 757 mAhg (1) at a current density of 100 mAg (1) and a good cycling performance at high current rates. (C) 2016 Elsevier Ltd. All rights reserved.

Hydrothermally synthesized fluorescent Zn2SnO4 nanoparticles for dye sensitized solar cells - Das, Partha Pratim; Roy, Anurag; Agarkar, Shruti; Devi, Parukuttyamma Sujatha (Dyes and Pigments, 2018)
In this work, we have investigated the interaction of hydrothermally synthesized Zn2SnO4 (ZTO) nanoparticles (NPs) with two different commercial photo sensitizers such as N719 and N3 dye molecules and studied their performance in dye sensitized solar cells (DSSC). Interestingly, the ZTO NPs exhibited band edge emission in the mid UVA region and as a result possibility of enhanced light harvesting in the terminal UVA region was anticipated in the device due to the efficient energy transfer observed in case of the sensitizer N719 than N3. The dye sensitization property has been found to be higher for the N3 dye molecules than the N719 dye molecules as based on the time dependent dye loading study. The devices fabricated with ZTO-N719 exhibited improved photovoltaic performance compared to the ZTO-N3 based devices exhibiting an overall conversion efficiency of 2.56% by the former compared to the later (1.90%) under 1SUN 1.5AM illumination and sensitization for 12 h.